A Maqashid Shariah Perspective on The Limitation of Subsidized Fuel (BBM) - Anisah Maharani Putri Werdani; M. Junaidi (Proceeding International Conference Restructuring and Transforming Law, 2025)
Fuel (BBM) is a vital commodity that significantly affects the livelihood of the general public. Currently, the use of subsidized fuel remains misdirected, with many financially capable individuals taking advantage of government-provided subsidies. Therefore, this paper seeks to examine the public benefit (maslahah) of limiting subsidized fuel distribution, in line with the objectives of maqashid shariah. This study employs a normative-juridical method using a descriptive-analytical approach, library research, and qualitative data analysis. The findings indicate that the concept of limiting subsidized fuel constitutes a maslahah dharuriyyah (essential benefit). According to the classification of Imam Al-Syatibi, this type of benefit, if neglected, can pose a threat to the safety of human life. The author argues that the policy of limiting subsidized fuel is an appropriate first step, as it impacts various sectors and prioritizes the public interest. Therefore, it is recommended that the government consistently socialize this policy to the community.